Implementation of direct investment law in Indonesia - Yevendri Yevendri (Gema Wiralodra, 2023)
By making the best use of investment and utilization of domestic and foreign capital, which is primarily directed at rehabilitation, renewal, expansion and development of new developments in the field of production of goods and services, our nation will be able to obtain the capital needed for economic development through investment. As a result, public capital is fully mobilized. The following are the objectives of this research: (1) To find out how the Investment Law is implemented in Indonesia; (2) To find out what obstacles the Indonesian Investment Law faces in its implementation; (3) To learn how to deal with the challenges posed by the implementation of Indonesia's Direct Investment Law. A qualitative normative juridical approach using primary data and secondary data is a research method. Article 2 of Law no. 25 of 2007 reflects the research findings: The provisions of this Law apply to all investments made within the territory of the Unitary State of the Republic of Indonesia. Weaknesses of legal institutions that become obstacles; in the legal system. Commitment to creating legal certainty through public information disclosure, while still paying attention to the interests of the community, is an effort that can be made to overcome this problem.